Bleaching internal pascaperawatan endodontik - Badi Soerachman (Makassar Dental Journal, 2018)
Discoloration of the teeth can occur due to several factors such as bleeding on the pulp, necrosis of the pulp, drugs, materials used in root canal treatment, and materials used for the restoration of the teeth. Discoloration of the teeth especially in anterior teeth greatly affects the aesthetic and the level of confidence in one's self. One of the ways that can be done is to restore colors with internal bleaching. The result obtained after performing the endodontic treatment and internal bleaching with one visit there is a significant colour change. The indication clinically shows one sign of success, so it can be used as one of the options in doing these treatments. Internal bleaching after endodontic treatment, using the technique of walking bleach, gives satisfactory results with a short time of visit and safe to use by following the proper procedure.